2015
DOI: 10.1377/hlthaff.2014.1055
|View full text |Cite
|
Sign up to set email alerts
|

Physician Characteristics Strongly Predict Patient Enrollment In Hospice

Abstract: Individual physicians are widely believed to play a large role in patients’ decisions about end-of-life care, but little empirical evidence supports this view. We developed a novel method for measuring the relationship between physicians’ characteristics and hospice enrollment in a nationally representative sample of Medicare patients with poor-prognosis cancer—for whom palliative treatment and hospice would be considered standard of care—who died in the period 2006–11. We found that the proportion of a physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 31 publications
3
63
1
Order By: Relevance
“…Our focus on symptoms leading to restricted activity enhances the clinical relevance of our findings because proper management of these symptoms may substantially improve quality of life while reducing caregiver burden. Although prior studies have demonstrated sex-specific differences in hospice referral and utilization, 21,22,24 we found no differences between men and women in the prevalence or mean number of restricting symptoms before and after the start of hospice.…”
Section: Discussioncontrasting
confidence: 93%
“…Our focus on symptoms leading to restricted activity enhances the clinical relevance of our findings because proper management of these symptoms may substantially improve quality of life while reducing caregiver burden. Although prior studies have demonstrated sex-specific differences in hospice referral and utilization, 21,22,24 we found no differences between men and women in the prevalence or mean number of restricting symptoms before and after the start of hospice.…”
Section: Discussioncontrasting
confidence: 93%
“…These findings may have policy implications because administrative-database indicators 4 are becoming increasingly feasible to assess with the expansion of electronic health records under the Health Information Technology for Economic and Clinical Health Act. This is particularly noteworthy given growing evidence that physicians’ characteristics and beliefs are one of the strongest predictors of end-of-life care, 20,21 suggesting that modifications to physicians’ practices may result in significant improvements.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of nearly 200 000 patients with metastatic cancer found that the single most influential factor in determining whether a patient died in hospice care was the lead physician's prior referral frequency to hospice. 5 Another study of nearly 22 000 Medicare patients with advanced NSCLC found that 43% received chemotherapy within 30 days of death and that after adjusting for other patient and physician characteristics, physician practice in a smaller independent office was a predictor of more aggressive care. 6 What motivates physicians to pursue or reject aggressive care is not known but could include factors such as personal beliefs, personality, knowledge deficits, and cognitive biases.…”
Section: Physician Practice Variation As a Force In Decision Makingmentioning
confidence: 99%